1992
DOI: 10.3168/jds.s0022-0302(92)77954-5
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Dairy Cows to Additions of Distillers Dried Grains with Solubles in Alfalfa-Based Diets

Abstract: Twenty-four Holstein cows in wk 3 through 12 of lactation were used to evaluate distillers dried grains with solubles as a protein source for alfalfa-based diets. Diets were formulated containing 0, 10.1, 20.8, or 31.5% distillers dried grains with solubles. Crude protein in these diets was 13.9, 16.0, 18.1, and 20.3%. Milk yield increased linearly with increasing dietary CP, whereas DMI was not affected. Dry matter intake averaged over 4% of BW for all treatments. Intake of undegraded intake protein was .93, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Total milk yield increased linearly (P = 0.02) with increasing concentrations of DDGS in the diet (27.4, 28.5, 29.3, and 30.6 kg/d for the control and 10, 20, and 30% DDGS). Similar milk responses have been noted in research by Anderson et al (2006), Clark andArmentano (1997), andGrings et al (1992). The increase in milk yield can be attributed to the increase in DMI and improved energy status.…”
Section: Milk Production and Compositionsupporting
confidence: 82%
See 2 more Smart Citations
“…Total milk yield increased linearly (P = 0.02) with increasing concentrations of DDGS in the diet (27.4, 28.5, 29.3, and 30.6 kg/d for the control and 10, 20, and 30% DDGS). Similar milk responses have been noted in research by Anderson et al (2006), Clark andArmentano (1997), andGrings et al (1992). The increase in milk yield can be attributed to the increase in DMI and improved energy status.…”
Section: Milk Production and Compositionsupporting
confidence: 82%
“…The linear increase in DMI may be due to the smaller particle size and increased passage rate with the DDGS compared with the control diet (Allen, 2000). Feeding DDGS has resulted in differing responses on DMI (Grings et al, 1992). Grings et al (1992) evaluated the effect on milk yield and milk composition of CP concentration in diets using increasing concentrations of DDGS.…”
Section: Feed Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of DDGS in finishing diets for beef cattle has been extensively researched, data evaluating supplemental DDGS for cattle consuming forage diets are limited. Grings et al (1992) reported no differences in DMI when lactating dairy cows fed alfalfa-based diets were supplemented with DDGS at 0, 10.1, 20.8, or 31.5% of diet DM as a replacement for ground corn. Conversely, when evaluating DDGS as a forage substi-tute, MacDonald and Klopfenstein (2004; 0 or 0.46% of BW daily as DDGS; smooth brome pastures) and Morris et al (2005;0, 0.24, 0.48, 0.71, or 0.95% of BW daily as DDGS; low-and high-quality forage diets), reported decreased forage intake with increasing levels of DDGS offered to heifers.…”
Section: Introductionmentioning
confidence: 98%
“…While in general DDGS appears a valuable source of energy and protein for ruminants, it is a feedstuff that greatly varies in nutrient content and protein and energy values (Westreicher‐Kristen et al., ). Some studies using dairy cows investigated the effect of partial substitution of protein sources of the diets by one corn‐DDGS (Grings et al., ; Anderson et al., ; Janicek et al., ), or by three different corn‐DDGS (Powers et al., ; Kleinschmit et al., ). However, to fully explore the potential of using DDGS, they should be included as the sole protein‐rich feed in dairy cow diets.…”
Section: Introductionmentioning
confidence: 99%